2012
DOI: 10.1128/jcm.05903-11
|View full text |Cite
|
Sign up to set email alerts
|

First Evaluation of an Improved Assay for Molecular Genetic Detection of Tuberculosis as Well as Rifampin and Isoniazid Resistances

Abstract: bThe commercially available line probe assay MTBDRplus 2.0 (Hain Lifescience, Nehren, Germany) was evaluated for its ability to detect Mycobacterium tuberculosis complex (MTBC) and mutations conferring resistance to rifampin (RMP) and isoniazid (INH) directly in smear-negative and smear-positive pulmonary clinical specimens under routine laboratory conditions. A total of 348 samples originating from Moldova, a high-incidence country for tuberculosis (TB), were investigated. Two hundred fiftyseven (73.9%) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 15 publications
7
73
4
1
Order By: Relevance
“…However, this percentage is greater than those reported in Republic of Moldova (0.9%) and Hungary (6.9%) (29,28). Other studies also mention low frequencies for this type of mutation in countries like: Italy (6.5%), South Africa (8.6%), China (10%), Ukraine (12.5%), Germany (13.6%) and Turkey (17.1%) (10,21,22,24,26,27).…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…However, this percentage is greater than those reported in Republic of Moldova (0.9%) and Hungary (6.9%) (29,28). Other studies also mention low frequencies for this type of mutation in countries like: Italy (6.5%), South Africa (8.6%), China (10%), Ukraine (12.5%), Germany (13.6%) and Turkey (17.1%) (10,21,22,24,26,27).…”
Section: Discussioncontrasting
confidence: 40%
“…This is in accordance with reports from other regions, such as China and South Africa (63.2% and 70.5%, respectively) (21,22) and some European countries: Turkey -56.1%, Italy -60.4%, Bulgaria -65%, Ukraine -73%, Germany -75.7% (10, 24 -27). However, our study showed great differences from our neighboring countries, Hungary with a lower frequency (31%) and Republic of Moldova with a higher frequency (86.8%) (28,29).…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…An early evaluation study on smear-negative samples indicated 90.7% sensitivity and 96% specifi city for rifampicin resistance, and 93.5% sensitivity and 82.3% specifi city for isoniazid resistance. 16 The use of the assay is technically more demanding and has a longer turn-around time compared with Xpert ® MTB/Rif, but is a good alternative test for isoniazid and rifampicin resistance in reference laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a limited number of assays have so far entered clinical laboratories. One example is Genotype MDRTBplus (Hain, Germany), which could detect both RIF and INH resistance mutations in a single assay and has been extensively validated (3)(4)(5)(6)(7). However, this reverse hybridization-based assay requires multiple post-PCR manipulations, and the color readout is subject to visual estimation.…”
mentioning
confidence: 99%